Exploring influenza vaccination determinants through digital participatory surveillance - Kathleen Kelley; Nicolò Gozzi; Mattia Mazzoli; Daniela Paolotti (BMC Public Health)
Abstract Background Vaccination is key for mitigating the impact of recurring seasonal influenza epidemics. Despite the efficacy and safety of influenza vaccines, achieving optimal vaccination uptake remains a challenge. This study aimed to explore the determinants of influenza vaccination uptake using data from Influweb, the Italian node of the Influenzanet participatory surveillance network. Methods This study utilizes a longitudinal dataset of self-reported vaccination statuses from Italian participants across the 2011–2021 flu seasons. Logistic regression models were used to identify factors associated with vaccination uptake. Post-stratification weights were applied to account for demographic differences between the Influweb sample and the general population. Results The analysis reveals that individuals using public transport and those living with minors are less likely to receive the influenza vaccination. On the other hand, university-educated individuals, and those on medication for chronic diseases are more likely to be vaccinated. Age also plays a role: individuals aged 44 and under are less likely to vaccinate compared to those aged 45–65, while those over 65 are more likely to do so. Furthermore, higher cumulative influenza-like illness incidence rates within a macro-region are associated with increased vaccination uptake. Finally, the impact of COVID-19 pandemic was associated with an increase in influenza vaccination uptake. Comparison of the Influweb data to vaccination rates reported by the Italian Health Ministry revealed higher coverage for self-reported vaccination. This could be linked to the voluntary nature of the survey, possibly attracting a more health-conscious cohort. Conclusions Our study found that individuals living with minors and those relying on public transportation have lower odds of being vaccinated, despite having a higher documented risk of respiratory virus exposure. These findings highlight the importance of continued public health efforts targeting vulnerable groups and raising awareness about the risks of forgoing vaccination. The complex interplay of socioeconomic, demographic, and public health context significantly shapes vaccination decisions, emphasizing the need for tailored public health campaigns.